2024
DOI: 10.3390/pharmaceutics16030409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatment with Sodium Dichloroacetate and Sodium Valproate on the Genes in Inflammation- and Immune-Related Pathways in T Lymphocytes from Patients with SARS-CoV-2 Infection with Pneumonia: Sex-Related Differences

Donatas Stakišaitis,
Linas Kapočius,
Vacis Tatarūnas
et al.

Abstract: The study presents data on the anti-inflammatory effects of a combination of sodium dichloroacetate and sodium valproate (DCA–VPA) on the expression of inflammation- and immune response-related genes in T lymphocytes of SARS-CoV-2 patients. The study aimed to assess the effects of DCA–VPA on the genes of cytokine activity, chemokine-mediated signaling, neutrophil chemotaxis, lymphocyte chemotaxis, T-cell chemotaxis, and regulation of T-cell proliferation pathways. The study included 21 patients with SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 141 publications
0
1
0
Order By: Relevance
“…Elucidating the evolution of GBM sex-linked dimorphism and the efficacy of treatments will be essential to improve the effectiveness of treatment and patient survival, and ensuring that personalized treatment based on specific molecular mechanisms of GBM is an essential challenge for further research [18]. Treatment with a combination of VPA and dichloroacetate significantly increased Slc5a8 gene expression and showed a significant anti-inflammatory effect on thymocytes from male mice [19], and treatment of T lymphocytes from males and females with this combination showed a significant anti-inflammatory effect and gender-related differences [20]. It was reported that different VPA effect the expression of the SLC12A2 (NKCC1) and SLC12A5 (KCC2) co-transporter genes in pediatric glioblastoma PBT24 (boys) and SF8628 (girls) cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the evolution of GBM sex-linked dimorphism and the efficacy of treatments will be essential to improve the effectiveness of treatment and patient survival, and ensuring that personalized treatment based on specific molecular mechanisms of GBM is an essential challenge for further research [18]. Treatment with a combination of VPA and dichloroacetate significantly increased Slc5a8 gene expression and showed a significant anti-inflammatory effect on thymocytes from male mice [19], and treatment of T lymphocytes from males and females with this combination showed a significant anti-inflammatory effect and gender-related differences [20]. It was reported that different VPA effect the expression of the SLC12A2 (NKCC1) and SLC12A5 (KCC2) co-transporter genes in pediatric glioblastoma PBT24 (boys) and SF8628 (girls) cells [21].…”
Section: Introductionmentioning
confidence: 99%